Development of augmented reality integrated physics e-worksheet to improve students' problem-solving skills - Rosalita Anggi Suryanto; Poppy Sari Dewi; Dadan Rosana (Universitas PGRI Kanjuruhan Malang, 2022)
The STEM approach through the augmented reality usage can provide visualization to students in online learning. The purposes of this research are to develop Physics E-Worksheet based on STEM using augmented reality system, and to improve the problem-solving skills of high school students on Momentum and Impulse material. The type of research used is research and development (R&D) with a 4D model (define, design, develop and disseminate). This study involved 24 students as a field trial class and 31 students in class X as a field operational class. The results of this study are: This Physics AR E-Worksheet is valid and reliable for use in the physics learning process for Momentum and Impulse material based on the results of validation analysis using an average value of a scale of four with a score of 3.73 in very good criteria. The results of the Paired T-Test analysis showed the value of Sig. 0.00, so that there is an effect of using AR Physics E-Worksheet on improving problem-solving skills of high school students. The score of Normalized Gain obtained 0.77 in high category improvement. The results showed that the AR Physics E-Worksheet was effective in improving problem solving skills so that it could be used as a learning medium for the Momentum and Impulse topic by class X science students.